Crystallization and characterization of nonlinear optical material: Glycolylurea - P.M. Anbarasan2, N. Sakthivel1* and (Recent Research in Science and Technology, 2011)
Glycolylurea an intriguing organic material for frequency conversion has been grown by slow evaporation solution growth technique at room temperature. The solubility studies have been carried out in the temperature range 30 - 60°C. Single crystals have been grown by slow evaporation method from deionised water. These crystals were characterized by FTIR, UV-Vis and Hardness studies. The crystal belongs to monoclinic with space group C12/c1. FTIR spectral studies were performed for conformation of the Glycolylurea molecule and hydrogen bonds. The optical transmission spectra of the grown crystal are tested by UV – vis spectrophotometer and found that the crystal was transparent over entire visible region. The mechanical response of the crystal has been studied using Vickers microhardness technique.